Analisis Ekonomi Kegiatan Penyuluhan Tentang Penerapan System Of Rice Intensification (SRI) di Tujuh Kabupaten Provinsi Bali: Analisis SEM - Adi Putra, I Gede Setiawan (Jurnal Ekonomi Kuantitatif Terapan, 2012)
Despite the SRI’s higher yield potential, the Subak member rice farmers are still reluctant to adopt this new way of cultivating rice. In about five years since its introduction to Bali, only 288 rice farmers have adopted it. This slow rate of adoption became a problem worth to investigate. In this conjunction, this study attempted to disclose the extent of SRI adoption amongst these farmers, and to explain how factors such as farmer’s personal characteristics, perceptions about SRI, attitudes toward SRI, Self-Reliance, and Extension workers’ as well as the heads of Subak competencies jointly affected the adoption behavior of the Balinese rice farmers. To attain these objectives an ex post facto study was designed. A random sample of 104 rice farmers was thereafter selected and interviewed using a structured questionnaire. Data were then analyzed by employing the Structural Equation Model (SEM) procedure with the Lisrel Version 8.3 program. The study concluded that the extent of adoption of the 9 components of SRI amongst the Balinese rice farmers were still diverse, and the intensity of the above factors’ effects on the SRI adoption amongst the Balinese rice farmers ranged from weak to moderate.
Keywords: SRI; Subak; Balinese rice farmers; economic; extension; SEM